Local diurnal upwelling driven by sea breezes in northern Monterey Bay - Woodson, C (2015)
Sea breezes often have significant impacts on nearshore physical and biological processes. We document the effects of a diurnal sea breeze on the nearshore thermal structure and circulation of northern Monterey Bay, California, using an array of moorings during the summer upwelling season in 2006. Moorings were equipped with thermistors and Acoustic Doppler Current Profilers (ADCPs) to measure temperature and currents along the inner shelf in the bay. Temperature and current data were characteristic of traditional regional scale upwelling conditions along the central California coast during the study period. However, large diurnal fluctuations in temperature (up to 5 1C) were observed at all moorings inshore of the 60-m isobath. Examination of tidal, current, temperature, and wind records revealed that the observed temperature fluctuations were the result of local diurnal upwelling, and not a result of nearshore mixing events. Westerly diurnal sea breezes led to offshore Ekman transport of surface waters. Resulting currents in the upper mixed layer were up to 0.10ms 1 directed offshore during the afternoon upwelling period. Surface water temperatures rapidly decreased in response to offshore advection of surface waters and upwelling of cold, subsurface water, despite occurring in the mid- afternoon during the period of highest solar heat flux. Surface waters then warmed again during the night and early morning as winds relaxed and the upwelling shadow moved back to shore due to an unbalanced onshore pressure gradient.